Neuronal regulation of the gut immune system and neuromodulation for treating inflammatory bowel disease. Issue 11 (27th August 2021) - Populin, Luis; Stebbing, Martin J.; Furness, John B.
Abstract: The gut immune system in the healthy intestine is anti‐inflammatory, but can move to a pro‐inflammatory state when the gut is challenged by pathogens or in disease. The nervous system influences the level of inflammation through enteric neurons and extrinsic neural connections, particularly vagal and sympathetic innervation of the gastrointestinal tract, each of which exerts anti‐inflammatory effects. Within the enteric nervous system (ENS), three neuron types that influence gut immune cells have been identified, intrinsic primary afferent neurons (IPANs), vasoactive intestinal peptide (VIP) neurons that project to the mucosa, and cholinergic neurons that influence macrophages in the external muscle layers. The enteric neuropeptides, calcitonin gene‐related peptide (CGRP), tachykinins, and neuromedin U (NMU), which are contained in IPANs, and VIP produced by the mucosa innervating neurons, all influence immune cells, notably innate lymphoid cells (ILCs). ILC2 are stimulated by VIP to release IL‐22, which promotes microbial defense and tissue repair. Enteric neurons are innervated by the vagus, and, in the large intestine, by the pelvic nerves. Vagal nerve stimulation reduces gut inflammation, which may be both by stimulation of efferent (motor) pathways to the ENS, and stimulation of afferent pathways that connect to integrating centers in the CNS. Efferent pathways from the CNS have their anti‐inflammatory effects through either or both vagal efferent neurons and sympathetic pathways. The final neurons in sympathetic pathways reduce gut inflammation by the action of noradrenaline on β2 adrenergic receptors expressed by immune cells. Activation of neural anti‐inflammatory pathways is an attractive option to treat inflammatory bowel disease that is refractory to other treatments. Further investigation of the ways in which enteric reflexes, vagal pathways and sympathetic pathways integrate their effects to modulate the gut immune system and gut inflammation is needed to optimize neuromodulation therapy.